FNDC-1-mediated mitophagy and ATFS-1 coordinate to protect against hypoxia-reoxygenation. Issue 11 (2nd November 2021) - Lim, Yunki; Berry, Brandon; Viteri, Stephanie; McCall, Matthew; Park, Eun Chan; Rongo, Christopher; Brookes, Paul S.; Nehrke, Keith
ABSTRACT: Mitochondrial quality control (MQC) balances organelle adaptation and elimination, and mechanistic crosstalk between the underlying molecular processes affects subsequent stress outcomes. FUNDC1 (FUN14 domain containing 1) is a mammalian mitophagy receptor that responds to hypoxia-reoxygenation (HR) stress. Here, we provide evidence that FNDC-1 is the C. elegans ortholog of FUNDC1, and that its loss protects against injury in a worm model of HR. This protection depends upon ATFS-1, a transcription factor that is central to the mitochondrial unfolded protein response (UPRmt). Global mRNA and metabolite profiling suggest that atfs-1 -dependent stress responses and metabolic remodeling occur in response to the loss of fndc-1 . These data support a role for FNDC-1 in non-hypoxic MQC, and further suggest that these changes are prophylactic in relation to subsequent HR. Our results highlight functional coordination between mitochondrial adaptation and elimination that organizes stress responses and metabolic rewiring to protect against HR injury. Abbreviations: AL: autolysosome; AP: autophagosome; FUNDC1: FUN14 domain containing 1; HR: hypoxia-reperfusion; IR: ischemia-reperfusion; lof: loss of function; MQC: mitochondrial quality control; PCA: principle component analysis; PPP: pentonse phosphate pathway; proK (proteinase K);UPRmt: mitochondrial unfolded protein response; RNAi: RNA interference.